The Impact of Indigenous Yeast on the Formation of Key Chemical Parameters in Saperavi Wine - Vepkhishvili, Nino; Kalandia, Aleko; Davitashvili, Magda ("Intercultural Dialogues" Transactions, 2025)
Twelve highest quality, classical red wines, all with protected designation of origin, are produced in Georgia from Saperavi grapes, which is a variety of ancient origin and broad significance. These wines are in high demand among both local and international consumers. However, despite their excellence, wines made from Saperavi cultivated in different micro-zones (terroirs) often show a noticeable uniformity in sensory characteristics. This has become a significant challenge for Georgian winemaking. According to enologists, one essential reason for this phenomenon is the widespread use of imported, commercially available dry yeast strains. To solve this issue, a research team from Telavi State University proposed developing and using indigenous cultured yeasts tailored to each specific micro-zone. This idea led to the creation of a fundamental scientific project, which in 2023 was awarded a three-year grant by the Shota Rustaveli National Science Foundation of Georgia. This research represents an unprecedented groundbreaking effort in the country: the isolation and development — for the first time — of distinct pure strains of Saccharomyces cerevisiae, specific to each Saperavi-growing micro-zone, previously nonexistent as pure cultures. As part of the project, tailored starter cultures were developed for ten distinct micro-zones. These yeast cultures have been studied microbiologically and identified through DNA. Wines were produced using these newly isolated strains, and their key technological parameters — including alcohol content, titratable acidity, volatile acidity, and extract — are presented in this paper. In parallel, wines made from the same raw materials using commercial yeast strains were also analyzed, in order to compare their characteristics with those of the wines fermented using the newly developed local cultures.